Distribution of Municipal Services and Some Factors Affecting Them (A survey in a sample of districts from Rushed municipal in Baghdad) - الطائي رعد عبد الله; السعدي زينب شميران (Journal of Economics and Administrative Sciences, 2014)
s The study aims to identify the fairness in the distribution of municipal services between municipal districts and areas, from point of view of municipal chamber staff and from the point of view of the citizen. It also aims to identify factors affecting the fairness of the distribution of municipal services. Municipal services were being studied : hygiene and waste, water supply, sewer, creating gardens, and street paving .Factors which examined its impact on municipal services are: resources available to municipal chamber, the managerial process at municipal chamber, and factors in the external environment surrounding municipal chamber.The results of the study showed that level of the equitable distribution of municipal services to various districts and areas were below average according to the opinions of employees in the municipal chamber while above average according to the opinions of citizens , and there is statistically significant variation between the views of the parties , staff and citizens ,about fairness in distribution of municipal services . Results showed also that there are a weakness in managerial process (planning, organization, leadership and control ) at the municipal chamber , low efficiency of the human resources available to municipal , lack of an effective and efficient system of information for decision-makers, and that those factors had a direct impact on the fairness in the distribution of municipal services distribution of municipal ervices.